Kelimpahan Mikroplastik pada Sedimen Ekosistem Terumbu Karang di Pulau Bokori Sulawesi Tenggara - Ilham Antariksa Tasabaramo; Mutmainnah Muchtar; Riska Riska; Lalang Lalang; Asni Asni (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2022)
Microplastic pollution is a threat to marine ecosystems. Microplatics in coral reef ecosystems can pose a threat to coral reef health. This study aims to determine the condition of coral reefs, and the distribution of microplastics in the tourist area of Bokori island as a first step for conservation and mitigation from the impact of microplastic pollution. Sampling wa carried out at 4 research stations. The environmental quality parameters measured were temperatur, dissolved oxygen, pH, salinity, water brightness, current, nitrate, and phosphate. Sampling using purposive sampling method. Sediment sampling using Scuba set and sediment grab at a depth of 3-10 meters. Sediment is taken ±1000 gr and stored in double zip lock plastic. The samples were the analyzed and observed using microplastics laboratory. The results showed that there are four types of microplastics found in sediments in the waters of the island of Bokori, namely fiber, foam, film, and fragments. Fiber is the most common type of microplastic with an average of 41.564 particles/kg dry sediment per aobservation station, while the lowest abundance was foam type with an average value of 9.379 particles/kg dry sediment. The abundance of microplastic at each sampling location was not the same due to the different characteristics of the study sites.